Cerita Rakyat Eyang Agung Lancing: Representasi Nilai-Nilai Budaya - Irma, Azizah; Pamungkas, Onok Yayang (RUANG KATA: Journal of Language and Literature Studies, 2023)
The folktale of Eyang Agung Lancing is a folktale that developed in Mirit village, Kebumen Regency. This folktale presents many cultural values. However, there has been no research on this subject. This study aims to describe the cultural values in the folklore of Eyang Agung Lancing. The researcher used literary anthropology approach to analyze the cultural values contained in the folklore of Eyang Agung Lancing. This research uses qualitative descriptive method. The data in this study are data in the form of utterances, phrases, clauses, and sentences sourced from the folklore book Mbah Lancing Penyebar Agama Islam di Urut Sewu by Aris Margono. Based on the results of data analysis in the folklore of Eyang Agung Lancing Kebumen Regency, it is found that there are cultural values grouped into five including (1) values related to the basic problems of human life there are 2 data, (2) values related to the basic problems of human work there are data, (3) cultural values of human nature with time there is 1 data, (4) values related to the basic problems between humans and the natural environment there is 1 data, and (5) values related to the basic problems between humans and their neighbors there are 5 data. The cultural value that dominates in this study is the cultural value related to the nature of human problems with others. It seems that this story has a strong spirit of harmonization. This is important for instilling character and social ethical attitudes. Therefore, an important implication of this study is that folktales can contribute to character to the community. Keywords: Cultural values, Folklore, Eyang Ageng Lancing